Mesenteric small cell lymphocytic lymphoma presenting as acute intestinal obstruction: A rare case scenario (Indian Journal of Case Reports, 2024)
Small-cell lymphocytic lymphoma is a rare type of B-cell non-Hodgkin lymphoma. It is known as one of the indolent lymphomas. Moreover, sigmoid volvulus as an initial presentation is extremely uncommon. We encountered a unique case of mesenteric small cell lymphocytic lymphoma that presented with sigmoid volvulus as the initial clinical presentation. A 55-year-old male presented with 7-day history of abdominal pain, abdominal distension for 6 days, and non-passage of stool and flatus with recurrent vomiting for 3 days. Abdominopelvic computed tomography revealed a distended small bowel with volvulus of sigmoid colon with twisting of its mesentery with inter-ileal as well as free peritoneal collections of fluid. A manual untwisting counterclockwise of the volvulus followed by resection and anastomosis at a point where the bowel has apparent normal thickness and color along with excisional biopsy of the enlarged lymph node. Histopathology confirmed the diagnosis of small-cell lymphocytic lymphoma. Mesenteric lymphomas are less likely to present with sigmoid volvulus as the initial clinical presentation due to their extraluminal location and also they are indolent in course. Early diagnosis and its management reduce morbidity and mortality.